Religious Romance & Epic Religion: About the Elusive Realm of Cult and the Arts (KULT_online, 2012)
This publication deals with the question of the similarities and differences between religious and literary imagination – a rather traditional question of the literary sciences. The multitude of diversely focused articles and materials presents at once the greatest potential and worst possible pitfall. It becomes clear how variously linked cult and the arts actually are, and how many points of convergence emerge, but also how many differences are to be stated that make processes of differentiation indispensable and absolutely necessary. However, it is exactly the contradictions and ambiguities that make this area of research so very fruitful and rewarding – just as this publication is.